Hybrid walnut : results from a five year field trial in southwest Sweden 2015-2020 - Juravle, Stefan (SLU/Southern Swedish Forest Research Centre, 2020)
A crossbreeding between american black walnut and Persian walnut lead to the development of a hybrid walnut (Juglans x intermedia). In a field trial from southwest Sweden have been tested the impact of different levels of nurse trees, fertilization and weed control on the early growth of two hybrid walnut varieties: NG23 and NG38. In order to quantify those effects, a series of qualitative and quantitative traits have been analysed. The results indicated that the hybrid NG38 has a more active change in height, compared to the other hybrid. Also, the mean total height reached by undamaged trees was higher for NG38 saplings. When it comes to qualitative assessments, NG38 had a lower number of branches and the thickest branches had a larger diameter. The NG23 walnuts have had significantly more branches and significantly lower diameters of the thickest branch. Damages occurred on the leading shoot were significantly less frequent on NG23 walnuts. The frequency of future crop trees also differed significantly between the two varieties, NG23 walnuts accounting for two thirds of the total number. Fertilization increased significantly the change in height, but also the frequency or the size of other less desirable characteristics. Trees that have been damaged at the top of the leading shoot during first growing season, turned into forked trees if fertilized. The number of branches and the diameter of branches were significantly larger on fertilised trees. Companion nurse trees influenced significantly and negatively the development of the walnuts. Considering these findings, can be concluded that both hybrids can establish and grow well in southwestern Sweden during juvenile stages, but in order to make unquestionable recommendations regarding long term management, more observations are needed.